XIMIYA SABAǴÍNDA INTEGRACIYALASQAN OQÍTÍW - Jarekeyeva, D.; Abdisattarova, E.; Sultanov, M. (SCIENCE and SOCIETY, 2024)
This article provides a brief definition of the concept “integration”. The integration of chemistry with biology, geography, everyday life, the environment, medicine, history and english is presented with examples to enhance the teaching of chemistry in school.